Small entrepreneurs of the Cisne 2 sector of the city of Guayaquil analysis of their socio-economic behavior (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2020)
The purpose of the research is to analyze the reality of small entrepreneurs in the sector of swan 2 of the city of Guayaquil, the present work is developed in order to describe the current situation of these small entrepreneurs and in this sense, a mapping is carried out of the characteristics, profiles, performance and levels of education of small entrepreneurs. On the other hand, the life experiences of emerging and existing entrepreneurs in the sector are highlighted; This is achieved through the application of surveys, which were used to study the conditions in which they are found both to define the quality of life of the sector, to the skills and abilities possessed by the population under study, which serves as an important input so that decision-makers can propose policies to help the entrepreneur's professional and competitive development and achieve a structural change in the Ecuadorian system at its higher levels, contributing to the development of the small entrepreneur and benefiting those people who are trained in different areas, who think about building your own source of work, that with capacity, creative ideas and values, try to form a small company and be a contribution to the economic growth of the country. The socio-economic study aims to leave a final report for entrepreneurs in the Cisne 2 sector of the city of Guayaquil, which they can take advantage of, in order to improve the socioeconomic conditions of the inhabitants of the sector, since they have a great influence on economic growth.
Keywords: entrepreneur; leadership; participatory action